Strategic Management Education of Thai Sangha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research was the objectives as follow, to study the educational administration of the Thai Sangha, to study theeducational management strategies of the Thai Sangha, and to propose educational management strategies of the Thai Sangha.This research was an integrated research which had an interview tool and uses descriptive and inferential statistics to analysesdata according to the quantitative research process. There were the amount 25 persons and took the results. The researchobtained from quantitative research, conducted in-depth interviews of 5 specific for question and content analysis. The resultsof the research revealed that the educational administration of all 4 Thai Sangha. They were appropriate at a high level, namelygeneral administration, academic administration budget management, and personnel management, respectively. The studyingof the educational management strategies for Thai Sangha, there were all 4 aspects namely, 1) organizing the curriculum inaccordance with the core. Curriculum was organizing learning-cantered learning and continuously. 2) The develop for aneducational quality assurance system made a budget plan. There was recruiting budgets through multiple channels and meetingfor expenditures once a month. 3) Developing human resource was developed plans an establish personnel according toknowledge, ability, and carry out the government. 4) There were regulations administrators have Dharma principles that setgoals according to the school's policy, and then stimulating desire through temptation. Strategies for educationaladministration of the Thai Sangha consisting of self-management, human resource management, and management with the aimof adjusting one's own attitudes and attitudes of colleagues, establishing working networks, developing personnel to meetcompetency, and planning management in all 4 areas through the PS-GANPPI MODEL to the efficiency of educationaladministration of the Phrapariyattidhamma schools General Education Department, model of sustainable from Thai Sangha.